Meneguhkan Bawaslu Sebagai “Lembaga Peradilan” dalam Bingkai Pengawasan Pemilu - Abdul Waid (Badan Pengawas Pemilihan Umum, 2018)
Law Number 7 of 2017 concerning on General Elections now has given strong authority to the Election Supervisory Agency (Bawaslu). The Election Supervisory Agency now does not only become a recommendation institution as stated in the previous Election law. Now the Election Supervisory Agency is the executor agency or case breaker. This was stated expressly in the formulation of Article 461 paragraph (1) of Law No.7 / 2017, that the Election Supervisory Agency, Provincial Election Supervisory Agency, Regency Election Supervisory Agency receive, examine, review, and decide election administration violations. Then paragraph 6 states that the decision of the Election Supervisory Agency, Provincial Election Supervisory Agency, Regency Election Supervisory Agency is to resolve election administration violations in the form of: first, administrative improvements to systems, procedures, or mechanisms in accordance with the provisions of the legislation; second, written warning; third, dissociate of certain stages in organizing elections; and fourth, other administrative sanctions in accordance with the provisions of the law. Based on that, this paper seeks to provide an analysis of the Election Supervisory Agency as an Election Supervisory Institution on the one hand, and as a judicial institution on the other side. The reason is that the Election Supervisory Agency now has a judicial function in implementing its authority, so that the procedure for resolving cases of election administration violations carried out in the Election Supervisory Agency is also in accordance with the judicial model of judicial institution in general. This paper also tries to confirm the performance of the Election Supervisory Agency as an institution that no longer needs to depend on the commitment of other institutions such as the KPU, the Police, and the prosecutor. Law No. 7/2017 has made the Election Supervisory Agency as the “real” supervisory institution. That is, the Election Supervisory Agency should be an institution that has an important role in realizing the implementation of the legitimate election system.